A Multi‐responsive Regenerable Europium–Organic Framework Luminescent Sensor for Fe3+, CrVI Anions, and Picric Acid. Issue 52 (17th November 2016) - Liu, Wei; Huang, Xin; Xu, Cong; Chen, Chunyang; Yang, Lizi; Dou, Wei; Chen, Wanmin; Yang, Huan; Liu, Weisheng
Abstract: A novel luminescent microporous lanthanide metal–organic framework (Ln‐MOF) based on a urea‐containing ligand has been successfully assembled. Structural analysis revealed that the framework features two types of 1D channels, with urea N−H bonds projecting into the pores. Luminescence studies have revealed that the Ln‐MOF exhibits high sensitivity, good selectivity, and a fast luminescence quenching response towards Fe 3+, Cr VI anions, and picric acid. In particular, in the detection of Cr2 O7 2− and picric acid, the Ln‐MOF can be simply and quickly regenerated, thus exhibiting excellent recyclability. To the best of our knowledge, this is the first example of a multi‐responsive luminescent Ln‐MOF sensor for Fe 3+, Cr VI anions, and picric acid based on a urea derivative. This Ln‐MOF may potentially be used as a multi‐responsive regenerable luminescent sensor for the quantitative detection of toxic and harmful substances. Abstract : Versatile MOF‐based sensor : A novel luminescent microporous lanthanide metal–organic framework based on a urea‐containing ligand has been successfully assembled and explored as a multi‐responsive regenerable luminescent sensor to detect Fe 3+, Cr VI anions, and picric acid (see graphic).